ANALISIS PENGENDALIAN KUALITAS PEMBUATAN WELLHUB DENGAN PENDEKATAN LEAN SIX SIGMA - HM. Ibnu Mastur; Nizar Filiawan Aji (Teknoin, 2016)
Wheel hub that is produced by PT. Yogya Presisi Tekniktama is a car wheel accessory that requires right size and striking shape, hence the need for accuracy of size is a must, so control should be maintained. Quality control is the way to determine the suitability between the standards that have been determined with the finished product that has been produced by PT. Yogya Presisi Teknikatama. The Six Sigma Motorolla method is employed for quality control.  From the diameter of Well hub, it can be identified that there is still DPMO of 42,700, the ability of the process is considered low enough with Cpm = 0.675, and the production process is unstable. While, defective products are caused by 5 types of origins with  DPMO of 34.126. The highest cause of defective products is caused by "Siloek". Proposed improvements to improve product quality, among others are; the machine repair on its holding pressure. While, in terms of method, the temperature of heater should be decreased to between 1-5º C.